Empirical analysis about the applicability of the CAPM model and the Three-factor model in China - Lin, Aidi (2018)
During the past two decades, many scholars have studied the applicability of the capital asset pricing theory in China. Thus, this topic is not that popular as before and the number of empirical tests of CAPM has declined in the past years. However, as the Chinese stock market develop rapidly these years, the efficiency of Chinese stock market changes a lot. Thus, the results of previous studies may no longer be applicable to the Chinese context. In this paper, I use the latest data to test the Capital Asset Pricing Model (CAPM) and Fama and French Three-Factor Model. For the test of CAPM model, I follow the method of Fama and MacBeth (1993) and conclude that the CAPM model does not perform well in my testing period. Beta is not the only determinant factor stock return. For the test of Three-factor model, I follow the analysis steps of Fama and French (1993). My result confirms the existence of size effect and book-to-market ratio effect on the stock return. Besides, the regression result implies that the Three-factor model has a better explanatory power than the CAPM model.